25th anniversary article CVD polymers: a new paradigm for surface modification and device fabrication - Coclite, Anna Maria (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.